Prenatal Diagnosis and Postnatal Findings of Bronchogenic Cyst - Livia Teresa Moreira Rios; Edward Araujo Júnior; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron; Marília da Glória Martins (Case Reports in Pulmonology)
Bronchogenic cysts arise from abnormal buds from the primitive esophagus and tracheobronchial tree, which do not extend to the site where alveolar differentiation occurs. Bronchogenic cysts are typically unilocular mucus field lesions arising from posterior membranous wall of the air way. The prenatal diagnosis usually is realized by two-dimensional ultrasound showing the large unilocular cystic image in the chest fetus. The prenatal percutaneous aspiration can reduce the risk of heart compression and permit better respiratory conditions to newborn. We present a case of a primiparous pregnant 23 year-old-woman prenatal ultrasound showed a large unilocular cyst in the left hemithorax with compression of the normal left lung tissue and contralateral mediastinal shift. This cyst was percutaneously aspirated without subsequent reaccumulation of fluid. The newborn did not have respiratory distress and the computed tomography scan confirmed the finding of a fluid-filled cyst in the left chest. The chest X-ray showed the displacement of the heart and the mediastinum from the left to the right. The prenatal diagnosis of bronchogenic cyst is very important to assess the degree of the compression of the normal lung and the mediastinum shift. Furthermore, the prenatal diagnosis permits planning delivery in the tertiary hospital with multidisciplinary team because of the risk of respiratory distress.